Comprehensive characterization of ERV-K (HML-8) in the chimpanzee genome revealed less genomic activity than humans - Wang, Chunlei; Zhai, Xiuli; Wang, Shibo; Zhang, Bohan; Yang, Caiqin; Song, Yanmei; Li, Hanping; Liu, Yongjian; Han, Jingwan; Wang, Xiaolin; Li, Jingyun; Chen, Mingyue; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Endogenous retroviruses (ERVs) originate from ancestral germline infections caused by exogenous retroviruses. Throughout evolution, they have become fixed within the genome of the animals into which they were integrated. As ERV elements coevolve with the host, they are normally epigenetically silenced and can become upregulated in a series of physiological and pathological processes. Generally, a detailed ERV profile in the host genome is critical for understanding the evolutionary history and functional performance of the host genome. We previously characterized and cataloged all the ERV-K subtype HML-8 loci in the human genome; however, this has not been done for the chimpanzee, the nearest living relative of humans. In this study, we aimed to catalog and characterize the integration of HML-8 in the chimpanzee genome and compare it with the integration of HML-8 in the human genome. We analyzed the integration of HML-8 and found that HML-8 pervasively invaded the chimpanzee genome. A total of 76 proviral elements were characterized on 23/24 chromosomes, including detailed elements distribution, structure, phylogeny, integration time, and their potential to regulate adjacent genes. The incomplete structure of HML-8 proviral LTRs will undoubtedly affect their activity. Moreover, the results indicated that HML-8 integration occurred before the divergence between humans and chimpanzees. Furthermore, chimpanzees include more HML-8 proviral elements (76 vs. 40) and fewer solo long terminal repeats (LTR) (0 vs. 5) than humans.These results suggested that chimpanzee genome activity is less than the human genome and that humans may have a better ability to shape and screen integrated proviral elements. Our work is informative in both an evolutionary and a functional context for ERVs.